2012
DOI: 10.1590/s0100-29452012000100029
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade e divergência genética entre genótipos de tucumanzeiro-do-pará (Astrocaryum vulgare Mart.) promissores para a produção de frutos por marcadores rapd

Abstract: RESUMO -O objetivo deste trabalho foi estimar a variabilidade e a divergência genética entre genótipos de tucumanzeiro-do-pará promissores para a produção de frutos por marcadores de RAPD. Foram coletadas amostras de folhas de 29 plantas-matrizes selecionadas no Banco Ativo de Germoplasma da Embrapa Amazônia Oriental, com base na produção de frutos por planta, mas com pronunciadas variações para outras características. As amostras de DNA foram amplificadas por 24 iniciadores RAPD e analisadas por três métodos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…According to Azevedo et al (2015), the expressive genetic variability found in sweet potatoes provides a large number of genotypes to be tested and evaluated to obtain new cultivars through selection and genetic improvement, thus constituting continuous and dynamic work. Oliveira et al (2012) report that studies on genetic variability and divergence are essential to advance new selection cycles, in addition to assisting in the identification and relationship between parents. σ² g = genetic variance; h 2 = heritability; CV g = genotypic coefficient of variation; CV g / CV e = relative coefficient of variation between CV g and CV e (experimental coefficient of variation); GS= selection gain; GS%= selection gain (percentage), given by SG% = SG ⁄ (mean gain)*100).…”
Section: Resultsmentioning
confidence: 99%
“…According to Azevedo et al (2015), the expressive genetic variability found in sweet potatoes provides a large number of genotypes to be tested and evaluated to obtain new cultivars through selection and genetic improvement, thus constituting continuous and dynamic work. Oliveira et al (2012) report that studies on genetic variability and divergence are essential to advance new selection cycles, in addition to assisting in the identification and relationship between parents. σ² g = genetic variance; h 2 = heritability; CV g = genotypic coefficient of variation; CV g / CV e = relative coefficient of variation between CV g and CV e (experimental coefficient of variation); GS= selection gain; GS%= selection gain (percentage), given by SG% = SG ⁄ (mean gain)*100).…”
Section: Resultsmentioning
confidence: 99%
“…A faster way is by using molecular markers such as in date palm (Phoenix dactylifera L.) (Elshibli and Korpelainen, 2008), coconut (Cocos nucifera L.) (Ribeiro et al, 2013) and tucumã-do-Pará palm (Astrocaryum vulgare Mart.) (Oliveira et al, 2012). However, in poorly studied species the evaluation using morphological and physiological characteristics of seeds and seedlings can be an interesting initial pathway.…”
Section: Introductionmentioning
confidence: 99%